Synthesis and Evaluation of Thiochroman-4-One Derivatives as Potential Leishmanicidal Agents - Vargas, Esteban (Molecules, 2017)
The S-containing heterocyclic compounds benzothiopyrans or thiochromones stand out as having promising biological activities due to their structural relationship with chromones (benzopyrans), which are widely known as privileged scaffolds in medicinal chemistry. In this work, we report the synthesis of 35 thiochromone derivatives and the in vitro antileishmanial and cytotoxic activities. Compounds were tested against intracellular amastigotes of Leishmania panamensis and cytotoxic activity against human monocytes (U-937 ATCC CRL-1593.2). Compounds bearing a vinyl sulfone moiety, 4h, 4i, 4j, 4k, 4l and 4m, displayed the highest antileishmanial activity, with EC(50) values lower than 10 μM and an index of selectivity over 100 for compounds 4j and 4l. When the double bond or the sulfone moiety was removed, the activity decreased. Our results show that thiochromones bearing a vinyl sulfone moiety are endowed with high antileishmanial activity and low cytotoxicity.